2012
DOI: 10.1364/ol.37.003303
|View full text |Cite
|
Sign up to set email alerts
|

Generation of super-length optical needle by focusing hybridly polarized vector beams through a dielectric interface

Abstract: A super-length optical needle (~14λ) of strong transversally polarized field with homogeneous intensity along the optical axis and subdiffraction beam size (~0.9λ) can be generated by focusing a hybridly polarized vector beam through a dielectric interface with an annular high-NA lens. Moreover, it is found that the polarization of the cross section near the focal plane is radial variant. Such a nondiffracting optical needle may have applications in atom-optical experiments, such as with atom trap and atom swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…To further improve the optical resolution, it would be attractive to a method of creating nondiffracting beams with sub-diffraction transverse dimensions. The generation of sub-wavelength 14 and sub-diffraction 15 optical needles has also been theoretically studied. Optical super-oscillation is referred to the optical phenomenon, in which the local spatial frequency of the optical field is larger than its global spatial frequency, and theoretically, it provides a possible means of creating arbitrary small features in far-field optics with the superposition of band-limited functions 16, 17 .…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the optical resolution, it would be attractive to a method of creating nondiffracting beams with sub-diffraction transverse dimensions. The generation of sub-wavelength 14 and sub-diffraction 15 optical needles has also been theoretically studied. Optical super-oscillation is referred to the optical phenomenon, in which the local spatial frequency of the optical field is larger than its global spatial frequency, and theoretically, it provides a possible means of creating arbitrary small features in far-field optics with the superposition of band-limited functions 16, 17 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the fundamental issues is whether the focal configurations would remain after passing through a boundary. Török et al [8], Gu [9], Novotny and Hecht [10], Pu and co-workers [11], and Biss and Brown [12] deduced rigorous solutions to the problem of focusing into an isotropic medium. However, there is a wide range of materials, such as uniaxial crystals (UCs), biaxial crystals, liquid crystals, fluorophores [13], and some biological tissues [14], possessing anisotropic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Kelei Hu etal investigated the focusing properties of a hybrid polarized beam through a dielectric interface focused by an annular high-NA lens. It is observed that the system generates a needle of transversally polarized field with homogeneous intensity long the optical axis with ultra-long focal depth of (∼14λ), and sub diffraction beam size of (∼0.9λ) 8 . Jianhua Shu etal illustrated that focusing of a double-ringshaped azimuthally polarized vector beam) through a dielectric interface focused by an annular high-NA objective lens can generate a ultra long focal hole (∼106λ) of sub wavelength size (∼0.5λ) 9 .…”
Section: Introductionmentioning
confidence: 99%